Validity of high-sensitivity C-reactive protein versus DAD equation for cardiovascular risk assessment in people living with HIV in Nigeria - Zainab Abdulkadir; Aminatu Ayaba Kwaku; Zainab Uba Ibrahim; Abdulgafar Lekan Olawumi; Zainab Abdulazeez Umar; Sherifah Sheriff; Safiya Usman Zahradeen; Fatimah Ismail Tsiga-Ahmed; Baba Maiyaki Musa; Mahmoud Umar Sani; Muktar Hassan Aliyu (BMC Infectious Diseases)
Abstract Background Cardiovascular risk assessment is challenging in people living with HIV (PLWH). The aim of this study is to determine the validity of high-sensitivity C-reactive protein (hsCRP) compared to the Data-collection on Adverse effects of Anti-HIV Drugs (DAD) equation for cardiovascular risk prediction in PLWH in Nigeria. Methods Using a cross-sectional study design, we systematically recruited 180 HIV-positive adults attending a tertiary hospital in Kano, Nigeria. We estimated the 5-year projected CVD risk for each participant using both the DAD equation and hsCRP. The performance of hsCRP as a new tool was then compared to the DAD equation (reference tool) by evaluating sensitivity, specificity and area under the curve (AUC) to discriminate performance. Results The mean age (± standard deviation) of the participants was 44.03 ± 10.58 years. The predictive accuracy of hsCRP for high CVD risk showed a specificity of 88.0%, sensitivity of 77.3%, and an AUC of 0.901 (95% confidence interval, CI: 0.824–0.978, p < 0.001) with hsCRP cut-off point for high risk set at > 3.03 mg/L. Comparison between the two models showed a moderate positive correlation (r = 0.58, p < 0.001) and fair agreement (κ = 0.26, p < 0.001). No factors significantly influenced the validity of hsCRP after regression modeling. Conclusion hsCRP is an excellent predictor of cardiovascular disease risk in PLWH, independent of traditional risk factors, comorbidities, and sociodemographic characteristics. Our findings suggest that hsCRP could be a feasible option for cardiovascular risk assessment in resource-limited settings, pending further validation in diverse populations.